The Implementation of Tiktok Application as a Medium for Developing Students’ English Speaking Skills - Adawiyah, Rabiatul; Dalimunthe, Ahmad Amin (Edukasi, 2024)
This study investigates the implementation of the TikTok application as a media to develop students' English-speaking skills. This study employs a descriptive qualitative methodology to examine the utilization of TikTok by high school students in Medan for English language practice. The study aims to understand the benefits gained and the challenges encountered by these students. Four students were observed and interviewed over the 2023/2024 academic year to collect data. These results indicated that students use TikTok to create and share videos, enhancing their speaking skills through stages such as pre-recording activities, during-recording activities, and post-recording activities. TikTok provides various advantages, such as increased self-confidence, improved vocabulary, better pronunciation and grammar mastery, and access to relevant references and ideas. However, students also face challenges like difficulties with grammar, pronunciation, selecting appropriate vocabulary, device problems, and unfamiliarity with TikTok features. This study asserts that TikTok provides notable benefits for English-speaking practice; addressing these challenges can further enhance its effectiveness as a learning tool.